Nhận diện tính cách thương hiệu điểm đến du lịch thành phố Hồ Chí Minh - Bui Ta Hoang , Vu (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2020)
In order to identify the personality of Ho Chi Minh city as a tourist destination and understand the overall evaluation of tourists regarding the brand image of the city, the research conducted both a qualitative study conducted among 60 tourists and 15 experts and a quantitative study among 400 domestic and international tourists. The results revealed 30 personality characteristics of Ho Chi Minh city, thereby identified 8 typical personality groups. The findings contribute to the formation of a tourist destination’s personality of Ho Chi Minh city, which was the first announced. Based on this findings, the managers in the sector could have better solutions and appropriate communication strategies in order to highlight the personality of the destination, contributing to identify the city’s tourism image.